2021
DOI: 10.3390/cancers13143405
|View full text |Cite
|
Sign up to set email alerts
|

Modified Tumor Budding as a Better Predictor of Lymph Node Metastasis in Early Gastric Cancer: Possible Real-World Applications

Abstract: Endoscopic resection (ER) is a minimally invasive treatment for early gastric cancer (EGC) with a low risk of lymph node metastasis (LNM). Recently, tumor budding (TB) has emerged as a potential predictor of LNM in EGC. We assessed the clinical significance of modified TB (mTB) that excludes the signet ring cell component and compared several TB assessment methods. Two hundred and eighty-nine patients with EGC at Uijeongbu St. Mary’s Hospital from 2010 to 2021 were enrolled. In univariate analysis, age, size, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 43 publications
(117 reference statements)
0
31
1
Order By: Relevance
“…Other differences in T stage, tumour site, and tumour site between intestinal-type and diffuse-type EEGC were reported in other studies ( 21 ). Unlike our previous knowledge that diffuse-type advanced GC was a risk factor for LNM ( 22 25 ), we found that intestinal type in EEGC was a risk factor associated with LNM ( 26 ). Other studies suggested a comparable rate of LNM between diffuse-type and intestinal-type GC for early-stage GC ( 21 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Other differences in T stage, tumour site, and tumour site between intestinal-type and diffuse-type EEGC were reported in other studies ( 21 ). Unlike our previous knowledge that diffuse-type advanced GC was a risk factor for LNM ( 22 25 ), we found that intestinal type in EEGC was a risk factor associated with LNM ( 26 ). Other studies suggested a comparable rate of LNM between diffuse-type and intestinal-type GC for early-stage GC ( 21 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Owing to its simplicity, TB-YN showed the highest reproducibility (I 2 = 0%) among all three methods. However, its accuracy is questionable because TBmimicking macrophages, tangentially sectioned glands, and/or apoptotic tumor cells can cause diagnostic errors [9,18,20]. TB was associated with poor OS and DFS regardless of the assessment method; however, standardization or consensus meetings for TB assessment for gynecologic cancers are still needed.…”
Section: Discussionmentioning
confidence: 99%
“…TB is a poor prognostic factor of survival that is correlated with clinical predictive factors such as T stage, lymph node metastasis (LNM), and lymphovascular invasion (LVI) in colorectal adenocarcinomas [6][7][8]. Emerging data suggest that TB is also correlated with such factors in gastric cancer (T stage, LNM, LVI) [9,10], lung cancer (T stage, pleural invasion, LNM, advance stage disease, LVI) [11], head and neck cancer (LNM, LVI, and PNI) [12,13], and breast cancer (T stage, LNM, LVI) [14,15]. The prognostic significance of TB has been explored in patients with gynecologic cancer, especially uterine cervical squamous cell carcinoma [16][17][18][19][20] and endometrial adenocarcinoma [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This might be because the TB-YN method is simple and more uniform than the TB-1HPF method. However, considering that TB imitators, like macrophages, tangentially sectioned tumor glands, or apoptotic tumor cells, can be interpreted as high-grade TB using the TB-YN method, dividing TB as present or absent could still result in an error ( 6 , 10 , 12 ). Therefore, standardization of the TB assessment method is urgently needed to predict a precise prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…TB is part of the tumor microenvironment (TME) and is related to epithelial–mesenchymal transition (EMT) ( 7 , 8 ). The prognostic significance of TB has been explored in solid cancers ( 7 ), such as colon cancer ( 9 , 10 ), gastric cancer ( 11 , 12 ), gynecologic cancer ( 13 , 14 ), and pancreatic cancer ( 15 ). Moreover, the prognostic significance of TBs and an association with EMT have also been explored in patients with lung cancer ( 16 25 ), but it has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%